2013
DOI: 10.1042/bj20130930
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 acts as a chaperone for the LDL receptor in the endoplasmic reticulum

Abstract: PCSK9 (proprotein convertase subtilisin/kexin type 9) binds to the LDLR (low-density lipoprotein receptor) at the cell surface and disrupts recycling of the LDLR. However, PCSK9 also interacts with the LDLR in the ER (endoplasmic reticulum). In the present study we have investigated the role of PCSK9 for the transport of the LDLR from the ER to the cell membrane. A truncated LDLR consisting of the ectodomain (ED-LDLR) was used for these studies to avoid PCSK9-mediated degradation of the LDLR. The amount of sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
2
30
0
3
Order By: Relevance
“…PCSK9 enhances LDLR lysosomal degradation, resulting in reduced LDL-C clearance, thereby leading elevated serum LDL-C levels [22, 23]. Functional mutations of PCSK9 could have a real impact on serum lipids level and cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…PCSK9 enhances LDLR lysosomal degradation, resulting in reduced LDL-C clearance, thereby leading elevated serum LDL-C levels [22, 23]. Functional mutations of PCSK9 could have a real impact on serum lipids level and cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…These findings lend support to the concept that PCSK9 secretion occurs in a highly regulated manner. A recent report has also suggested that the ectodomain of the LDL-R acts as a chaperone for PCSK9 folding and cleavage, increasing throughput from the proPCSK9 form to the cleaved mature form (41). Furthermore, mutations in the CHR domain, which do not affect self-proteolysis, have been noted to cause PCSK9 loss-of-function by interfering with the secretion pathway (42).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that binding of PCSK9 to the LDLR in the endoplasmic reticulum promotes autocatalytic cleavage of PCSK9 [27], [28]. Thus, reduced binding of PCSK9 to the LDLR in the presence of Pro31–52, could explain the inhibitory effect of this segment both on the autocatalytic cleavage and on the affinity to bind to the LDLR at the cell surface.…”
Section: Discussionmentioning
confidence: 99%